SLB Autism YPPA Kota Solok: Creating Pathways to Independence for Children with Special Needs - syabra, hanafi; Fitrtiani, Wahidah; Yeni, Putri; Li, Zhang; Tan, Ethan (Yayasan Minang Darussalam, 2025)
This research delves into how education is provided to children with special needs (CSN) at SLB Autism YPPA in Kota Solok, with the objective of fostering students' independence. Through observations, interviews, and systematic literature reviews, the study investigates critical aspects such as teachers' understanding of CSN, identifying students' interests and abilities, strategies for addressing children's issues, teaching methodologies, and their integration into inclusive education. Results show that SLB Autism YPPA Kota Solok adopts a personalized approach tailored to each student's individual needs, employing the Merdeka Curriculum and playful methods to enhance effective communication. Regular comprehensive evaluations focus on each student's unique potential. Nevertheless, there are ongoing challenges in inclusive education implementation, including the risk of inadvertent exclusion. The study highlights the necessity of a profound understanding of CSN, enhancing teacher skills, and creating a supportive inclusive environment to promote CSN's independence.